2014
DOI: 10.1073/pnas.1404654111
|View full text |Cite
|
Sign up to set email alerts
|

SPX1 is a phosphate-dependent inhibitor of PHOSPHATE STARVATION RESPONSE 1 in Arabidopsis

Abstract: To cope with growth in low-phosphate (Pi) soils, plants have evolved adaptive responses that involve both developmental and metabolic changes. PHOSPHATE STARVATION RESPONSE 1 (PHR1) and related transcription factors play a central role in the control of Pi starvation responses (PSRs). How Pi levels control PHR1 activity, and thus PSRs, remains to be elucidated. Here, we identify a direct Pi-dependent inhibitor of PHR1 in Arabidopsis, SPX1, a nuclear protein that shares the SPX domain with yeast Pi sensors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
407
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(437 citation statements)
references
References 56 publications
16
407
0
1
Order By: Relevance
“…Many significant advances have been achieved in our understanding of the signaling mechanisms that regulate the transcriptional activation of PSR genes, including the characterization of the central regulator PHR1 and its interaction with SPX1 and SPX2 repressors to control the activation of PSR genes (37). Our results showed that the mechanisms that regulate Arabidopsis responses to Pi starvation also involve changes in the DNA methylation status, thereby modulating the expression of PSR genes and root system developmental responses to low Pi availability.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Many significant advances have been achieved in our understanding of the signaling mechanisms that regulate the transcriptional activation of PSR genes, including the characterization of the central regulator PHR1 and its interaction with SPX1 and SPX2 repressors to control the activation of PSR genes (37). Our results showed that the mechanisms that regulate Arabidopsis responses to Pi starvation also involve changes in the DNA methylation status, thereby modulating the expression of PSR genes and root system developmental responses to low Pi availability.…”
Section: Discussionmentioning
confidence: 77%
“…Of particular interest is the finding that two key regulators of Arabidopsis responses to low Pi were among the Pf-methDEGs, namely SPX2, which inhibits PHOSPHATE STARVATION RESPONSE 1 (PHR1) DNA-binding activity in a Pi-dependent manner (37), and miR827 (38,39), which posttranscriptionally represses NITROGEN LIMITATION ADAPTATION (NLA) to release the negative regulation of PHOSPHATE TRANSPORTER1 (PHT1.1) and PHOSPHATE TRANSPORTER TRAFFIC FACILITATOR1 (PHF1), both of which are involved in Pi transport (39). The differential methylation changes observed in these two genes were highly consistent among tissues and over time under the LP conditions.…”
Section: Factor Analysis Of Methylomes Reveals a Discrete Set Of Pi Fmentioning
confidence: 99%
“…Thus, CK2, PHO2, and NLA generate a negative feedback loop for the regulation of PT activity according to plant Pi status. Such a negative loop is paralleled by a similar feedback mechanism for transcriptional control generated between the PHR1 master regulator of Pi starvation responses and several SPX proteins (Lv et al, 2014;Puga et al, 2014;Wang et al, 2014).…”
Section: Phosphorylation Of Pts Is Dependent On Pi Supplymentioning
confidence: 99%
“…Furthermore, their corresponding mutants exhibit altered gene induction and classical Pi starvation responses, including diminished effects on Pi content and lipid remobilization (Pant et al, 2015). Candidates for the systemic control of Pi starvation responses have been proposed, including substantial transport of mRNAs throughout the plant (as reviewed in Puga et al, 2017), and the direct sensing of Pi concentration (or Pi-containing metabolites) by SPX-type proteins (Wang et al, 2009;Puga et al, 2014;Wild et al, 2016).Two phosphatases belonging to the haloacid dehalogenase (HAD) superfamily were identified as some of the most strongly induced transcripts following Pi starvation (Bari et al, 2006;Müller et al, 2007;Thibaud et al, 2010). These enzymes were named PPsPase1 (for pyrophosphatase [PPi]-specific phosphatase1) and PECP1 (for phosphoethanolamine (PEth)/ phosphocholine [PCho] phosphatase1) on the basis of their in vitro activity, following their heterologous expression in bacteria and subsequent purification (May et al, 2011(May et al, , 2012.…”
mentioning
confidence: 99%
“…Furthermore, their corresponding mutants exhibit altered gene induction and classical Pi starvation responses, including diminished effects on Pi content and lipid remobilization (Pant et al, 2015). Candidates for the systemic control of Pi starvation responses have been proposed, including substantial transport of mRNAs throughout the plant (as reviewed in Puga et al, 2017), and the direct sensing of Pi concentration (or Pi-containing metabolites) by SPX-type proteins (Wang et al, 2009;Puga et al, 2014;Wild et al, 2016).…”
mentioning
confidence: 99%